Fanaticism : on the uses of an idea - Toscano, Alberto (London ; New York : Verso, 2010)
Fanaticism is usually seen as a deviant or extreme variant of an already irrational set of religious beliefs. This book explores the critical role fanaticism played in forming modern politics and the liberal state, and undermines the idea that liberalism and fanaticism are irrevocably opposed. ##Figures of extremism -- The birth of modern politics out of the spirit of millenarianism -- Raving with reason : fanaticism and enlightenment -- The revolution of the East : Islam, Hegel, psychoanalysis -- The clash of abstractions : revisiting Marx on religion -- The Cold War and the Messiah : on political religion.
boek